Comparative Study of the Results of a Three-year Observation of Cardiologists and Surgeons in Patients with Peripheral Atherosclerosis - L. S. Barbarash; A. N. Sumin; Yu. D. Medvedeva; E. V. Korok (Рациональная фармакотерапия в кардиологии, 2019)
Aim. To compare the results of 3-year follow-up of patients with peripheral atherosclerosis (PA) in two patient cohorts: during outpatient monitoring by cardiologists and when observed by surgeons.Material and methods. The first group included 131 patients with PA who sought medical attention in outpatient clinic in 2013-2014 and then were observed by a surgeon. The second group is represented by 454 patients with PA who sought medical attention in outpatient clinic in 2010- 2012 and then underwent observation by a cardiologist as a part of a pilot project. The average follow-up duration in the studied groups was three years. The groups were compared according to the main demographic, anthropometric indicators, the presence of risk factors for atherosclerosis, comorbidity, the prevalence of atherothrombotic events in history, laboratory and instrumental examination data. Additionally, after 3 years of observation the incidence of deaths and amputations was assessed in groups.Results. Patients of the second group were older than these in the first group (p<0.001). Patients of the group 1 compared to the group 2 were more often overweight (p=0.005), suffered from diabetes mellitus (p<0.001), had a disability (p<0.001). Among patients of the group 2 compared with the group 1, the clinical picture of angina pectoris (p=0.001), rhythm disorders (p=0.058) were more often observed, they had a greater number of myocardial infarctions (p<0.001) and myocardial revascularization operations in the history: coronary bypass surgery (p=0.029), percutaneous coronary interventions (p<0.001), and underwent coronary angiography (p<0.001). Patients in group 2 were more likely to receive statins (p<0.001), β-blockers (p<0.001), angiotensin-converting enzyme inhibitors, and calcium channel blockers, angiotensin II receptor blockers, and antiarrhythmics (p<0.001). Pentoxifylline was prescribed more often in the first group (p<0.001). With a three-year observation of PA patients a fatal outcome occurred in 8.2% of cases, amputation – in 1.4%. In the first group, compared with the second one, there were more often observed deaths in general (p=0.023), death from cardiac causes, stroke, disability (p=0.005) and amputations (p=0.003). The risk of adverse outcomes (death and amputations) was increased in the presence of signs of chronic lower limb ischemia of stage III, a history of amputation, more than 70% stenosis and occlusions of lower limb arteries, chronic lung disease, and angina symptoms. The risk of adverse outcomes was decreased in outpatient observation by cardiologist, taking statins, aspirin, and performing exercise therapy.Conclusion. Observation of PA patients by a cardiologist results in more frequent optimal drug therapy (due to the better adherence of cardiologists to clinical recommendations for the treatment of such patients) and improves the prognosis of these patients.